2011
DOI: 10.1007/s00170-011-3647-1
|View full text |Cite
|
Sign up to set email alerts
|

An image-based methodology to establish correlations between porosity and cutting force in micromilling of porous titanium foams

Abstract: Porous titanium foam is now a standard material for various dental and orthopedic applications due to its light weight, high strength, and full biocompatibility properties. In practical biomedical applications, outer surface geometry and porosity topology significantly influence the adherence between implant and neighboring bone. New microfabrication technologies, such as micromilling and laser micromachining opened new technological possibilities for shape generation of this class of products. Besides typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…9 The term pore filling in these cases is used to describe the irregular plowed surfaces. Tutunea-Fatan et al 12 and Fakhri et al 13 have shown that in micro processing of porous titanium foams (54% porosity), the large size of the pores in the workpiece (0.5–1.5 mm) and the small size of the cutting tool (less than 1 mm diameter) lead to discontinuity in the cutting process. The fine folds created in the material result in filling of the surface pores.…”
Section: Introductionmentioning
confidence: 99%
“…9 The term pore filling in these cases is used to describe the irregular plowed surfaces. Tutunea-Fatan et al 12 and Fakhri et al 13 have shown that in micro processing of porous titanium foams (54% porosity), the large size of the pores in the workpiece (0.5–1.5 mm) and the small size of the cutting tool (less than 1 mm diameter) lead to discontinuity in the cutting process. The fine folds created in the material result in filling of the surface pores.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium, ferrous alloys, and ceramic are used as the predominant porous materials in bone engineering and have received significant research attention. 1316 Jasperson et al 13 compared micro-pin-fin and micromachining considering thermal–hydraulic performance and manufacturability. Shen and Brinson 14 studied the finite element modeling of porous titanium.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructure-level machining modeling of ferrous alloys was investigated by Chuzhoy. 15 Abolghasemi Fakhri et al 16 used an image-based methodology to establish correlations between porosity and cutting force in micro-milling of porous titanium foams. Sharma et al 17 presented an experimental work on wire electrical discharge machining process which identifies the influence of process parameters that affect the cutting rate, dimensional shift, and surface roughness while machining of porous nickel–titanium (Ni40Ti60) alloy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations